Heat transfer in eccentric-concentric rotation of a disk and fluid at infinity - Khan, I. (American Scientific Publishers, 2016)
Heat transfer due to free convection flow in eccentric-concentric rotation of a disk and fluid at infinity is studied in this work Exact solutions for velocity and temperature are obtained by using the Laplace transform technique. The performed calculations disclose that the free convection parameter, Prandtl number, radiation parameter, and dimensionless time have strong influence on fluid velocity and temperature. The graphs are presented for such influence and examined carefully. Â© Copyright 2016 American Scientific Publishers All rights reserved.